سوسيولوجيا الحراك العربي من منظور بنيوي وظيفي - سعداوي, عمر (جامعة الوادي University of Eloued, 2019)
خلفت الحركات الاحتجاجية التي عرفتها بعض الدول العربية بعد 2010 فوضى مفاهيمية تحتاج إلى ضبط، من خلال ذلك يسعى هذا المقال إلى تتبع حركة مفهوم "الحراك العربي" ومدى استناد المفهوم إلى مرجعيات فكرية منسجمة وصلبة، وهو الأمر الذي يتطلب مراجعة المجال المعرفي العربي بما يمكننا من استيعاب الواقع السوسيولوجي في مستواه الابستمولوجي، لنصل في نهاية المقال إلى مدى حاجتنا إلى نهج "اركولوجي" للحفر في طبقات الفكر العربي لنتوصل إلى رؤية داخلية من رحم الواقع العربي يمكنها أن تؤصل لظاهرة الحراك وتخلصنا من حالة "الاغتراب" بين المستويين الابستمولوجي والانطولوجي. After the 2010 protests, the Arab countries have known a conceptual chaos which needs to be reconceptualized. In the light of this situation, this essay seeks to follow the evolution of the concept of "Arab movement" and to discuss the compatibility and durability of its intellectual backgrounds. This aim requires a review of Arab knowledge literature in order to understand the Arab sociological reality. Eventually, the study had concluded that we need an archeological approach for deep digging in Arab thought, to build a theoretical basis burning out of Arab reality, thereby reducing the "Alienation" state between the epistemological and the ontological levels.
Keywords: حراك عربي ; أمن ; تهديد ; تغيرات ; مقاربة عربية